(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English is widely regarded as the global language, serving as a crucial tool for communication in various fields, including business, education, science, and technology. As the most commonly spoken second language, it bridges cultural and linguistic gaps, enabling people from different backgrounds to interact and collaborate. The dominance of English in international trade, diplomacy, and digital communication highlights its importance in fostering global connections. This article explores the role of English as a universal medium, emphasizing its impact on crosscultural understanding, economic growth, and access to knowledge. Understanding and mastering English can open doors to global opportunities, making it an essential skill in today’s interconnected world.